Large-size free-standing single-crystal β-Ga2O3 membranes fabricated by hydrogen implantation and lift-off. Issue 19 (6th April 2021) - Zheng, Yixiong; Feng, Zixuan; Bhuiyan, A. F. M. Anhar Uddin; Meng, Lingyu; Dhole, Samyak; Jia, Quanxi; Zhao, Hongping; Seo, Jung-Hun
Abstract : This paper reports the first successful demonstration of large-size free-standing single-crystal β-Ga2 O3 NMs fabricated by the hydrogen implantation and lift-off process directly from MOCVD grown β-Ga2 O3 epifilms on native substrates. Abstract : In this paper, we demonstrated large-size free-standing single-crystal β-Ga2 O3 NMs fabricated by the hydrogen implantation and lift-off process directly from MOCVD grown β-Ga2 O3 epifilms on native substrates. The optimum implantation conditions were simulated with a Monte-Carlo simulation method to obtain a high hydrogen concentration with a narrow ion distribution at the desired depth. Two as grown β-Ga2 O3 samples with different orientations ([100] and [001]) were used to successfully create 1.2 μm thick β-Ga2 O3 NMs without any physical damage. These β-Ga2 O3 NMs were then transfer-printed onto rigid and flexible substrates such as SiC and polyimide substrates. Various material characterization studies were performed to investigate their crystal quality, surface morphologies, optical properties, mechanical properties, and bandgaps before and after the lift-off and revealed that the good material quality was maintained. This result offers several benefits in that the thickness, doping, and size of β-Ga2 O3 NMs can be fully controlled. Moreover, more advanced β-Ga2 O3 -based NM structures such as (Al x Ga1− x )2 O3 /Ga2 O3 heterostructure NMs can be directly created from their bulk epitaxy substrates; thus this study provides a viable route for the realization of high performance β-Ga2 O3 NM-based electronics and optoelectronics that can be built on various substrates and platforms.